2017
DOI: 10.1111/gwat.12514
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Investigation of Bedrock Heterogeneity/Unconformities at a DNAPL‐Impacted Site

Abstract: Organic solvent (i.e., dense nonaqueous phase liquid, DNAPL) migration in the subsurface is known to be extremely sensitive to geologic heterogeneity. There is often a focus on heterogeneity that results from changing depositional conditions over short spatial scales. Similar or even more extreme spatial heterogeneity can result postdeposition due to erosional processes. This study applies a synergistic approach based on a combination of high-resolution lithologic logs of continuous cores, borehole geophysical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The reference σ ranged from 6.74 × 10 −3 to 3.35 × 10 −4 S/m. The order‐of‐magnitude variation of σ was similar with the variation in some DNAPL‐contaminated field studies (e.g., Kuras et al, 2016; Steelman et al, 2017). The mean of the reference ln K i field was −10.5 (i.e., K mean = 2.75 × 10 −5 m/s), which was representative of the aquifer in Savannah River site in South Carolina (Hodges & Falta, 2001).…”
Section: Numerical Experimentssupporting
confidence: 81%
“…The reference σ ranged from 6.74 × 10 −3 to 3.35 × 10 −4 S/m. The order‐of‐magnitude variation of σ was similar with the variation in some DNAPL‐contaminated field studies (e.g., Kuras et al, 2016; Steelman et al, 2017). The mean of the reference ln K i field was −10.5 (i.e., K mean = 2.75 × 10 −5 m/s), which was representative of the aquifer in Savannah River site in South Carolina (Hodges & Falta, 2001).…”
Section: Numerical Experimentssupporting
confidence: 81%
“…The graphical shading log approach introduced here was developed through trial and error by the people doing the logging at three sites where research was being conducted on the transport and fate of organic contaminants in sedimentary rock (Parker et al 2012): the Wisconsin site (WI site), the California site (CA site), and the Ontario study area (ON study area). Hydrogeologic research at the WI site is focused on a mixed organic solvents DNAPL source zone and the associated dissolved phase plumes (Lima et al 2012;Steelman et al 2017;Lima et al 2018;Steelman et al 2020) migrating through nearly flat lying Cambrian and Ordovician siliciclastic rocks deposited in an epeiric sea overlain by Quaternary unconsolidated sediments deposited in an ice marginal setting (Meyer et al 2008(Meyer et al , 2016Harvey et al 2019). Studies at the CA site are focused on transport and fate of TCE through a turbidite sequence of Cretaceous siliciclastic rocks dipping at 30° (Sterling et al 2005;Cilona et al 2016;Pierce et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The electrolyte consisted of a 0.013 mol/L solution of NaCl with a resistivity of 4.4 Ω m at 20°C. Noted that the pore fluid used here is quite conductive (4.4 Ω m), it is because the resistivity of the pore fluid in organic contaminant fields is often lower than 10 Ω m. For instance, Steelman et al (2017) reported the resistivity of the groundwater in a DNAPL contaminant field ranges from 1.6 to 10.0 Ω m. Revil et al (2013) reported the resistivity of the pore fluid in former S-3 ponds contaminant field ranged from 1.0 to 12.5 Ω m.…”
Section: Sandbox Setupmentioning
confidence: 99%
“…Compared with traditional investigation methods (e.g., intrusive drilling and sampling method), non-invasive geophysical methods (especially electrical resistivity tomography, ERT) have already been applied to the monitoring of DNAPL-contaminated sites. This is due to the low-cost and high sampling density of these non-intrusive method in characterizing the morphology of contaminant plumes (Chambers et al, 2010;Naudet et al, 2014;Steelman et al, 2017). Despite these advances, challenges still exist for practical ERT applications.…”
Section: Introductionmentioning
confidence: 99%